Members of the Merozoite Surface Protein 7 Family with Similar Expression Patterns Differ in Ability To Protect against Plasmodium yoelii Malaria - Mello, Kerrianne (American Society for Microbiology, 2004)
Previously, we described the isolation of the Plasmodium yoelii sequence-related molecules P. yoelii MSP-7 (merozoite surface protein 7) and P. yoelii MSRP-2 (MSP-7-related protein 2) by their ability to interact with the amino-terminal end of P. yoelii MSP-1 in a yeast two-hybrid system. One of these molecules was the homologue of Plasmodium falciparum MSP-7, which was biochemically isolated as part of the shed MSP-1 complex. In the present study, with antibodies directed against recombinant proteins, immunoprecipitation analyses of the rodent system demonstrated that both P. yoelii MSP-7 and P. yoelii MSRP-2 could be isolated from parasite lysates and from parasite culture supernatants. Immunofluorescence studies colocalized P. yoelii MSP-7 and P. yoelii MSRP-2 with the amino-terminal portion of MSP-1 and with each other on the surface of schizonts. Immunization with P. yoelii MSRP-2 but not P. yoelii MSP-7 protected mice against a lethal infection with P. yoelii strain 17XL. These results establish that both P. yoelii MSP-7 and P. yoelii MSRP-2 are expressed on the surface of merozoites and released from the parasite and that P. yoelii MSRP-2 may be the target of a protective immune response.